Нейроімунологічний дисбаланс у хворих на хронічний панкреатит = Neuroimmunologic disbalance in patients with acute pancreatitis - Gorbunov, A. A. (Journal of Education, Health and Sport, 2016)
Gorbunov A. A. Нейроімунологічний дисбаланс у хворих на хронічний панкреатит = Neuroimmunologic disbalance in patients with acute pancreatitis. Journal of Education, Health and Sport. 2016;6(7):154-163. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57299 http://ojs.ukw.edu.pl/index.php/johs/article/view/3674 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.06.2016. Revised 09.07.2016. Accepted: 09.07.2016. УДК: 616.37- 002-036.11 НЕЙРОІМУНОЛОГІЧНИЙ ДИСБАЛАНС У ХВОРИХ НА ХРОНІЧНИЙ ПАНКРЕАТИТ А. А. Горбунов Одеський національний медичний університет, Одеса Резюме У ретроспективному аспекті оцінені були імунологічні показники хворих на хронічний панкреатит, оскільки автор припускав вирішальний вплив імунологічної реактивності організму і її «зламу» в патогенезі можливих ускладнень і летальності в післяопераційному періоді. Для досягнення мети клінічного спостереження хворі були розділені на 2 клінічні групи - 96 пацієнтів зі сприятливим (1-я група) і 21 пацієнт з ускладнененим (2 група) перебігом післяопераційного періоду (в тому числі померлі пацієнти). Отримані дані свідчать про те, що імунологічна реактивність організму хворих протягом післяопераційного періоду детермінує клінічний характер його перебігу. Це підтверджується сприятливим перебігом післяопераційного періоду у хворих з відновленими після оперативних втручань з приводу хронічного панкреатиту показниками клітинного та гуморального імунітету, а також його дисбалансом і ареактівністю при формуванні післяопераційних ускладнень, а також в разі гібелі пацієнтів. Автор робить висновок, що оцінка функціонального стану імунної системи є вирішальним критерієм в аспекті прогнозування характеру перебігу післяопераційного періоду. Ключові слова: хронічний панкреатит, імунологічна реактивність, клітинниі і гуморальний імунітет, післяопераційний період, критерії прогнозування. NEUROIMMUNOLOGIC DISBALANCE IN PATIENTS WITH ACUTE PANCREATITIS A. A. Gorbunov Odessa National Medical University, Odessa Summary In a retrospective aspect were evaluated immunological parameters in patients with chronic pancreatitis, because the author has assumed a decisive influence immunological reactivity of the organism and its "failure" in the pathogenesis of complications and mortality in the postoperative period. To achieve the goal of clinical observation, the patients were divided into 2 clinical group - 96 patients with a favorable (group 1) and 21 patients with complications of (Group 2) over the postoperative period (including deceased patients). The findings suggest that the immunological reactivity of patients in the postoperative period determines the clinical nature of its course. This is supported by a favorable course of the postoperative period in patients with restored after surgery for chronic pancreatitis indicators of cellular and humoral immunity, as well as its imbalances and areactivity the formation of post-operative complications, as well as in the case of death of patients. The author concludes that the assessment of the functional state of the immune system is a decisive criterion in the aspect of predicting the nature of postoperative period. Key words: chronic pancreatitis, immunologic reactivity, cellular and humoral immunity, afteroperational period, prognostic criteria. Резюме НЕЙРОИММУНОЛОГИЧЕСКИЙ ДИСБАЛАНС У БОЛЬНЫХ ХРОНИЧЕСКИМ ПАНКРЕАТИТОМ. В ретроспективном аспекте оценены были иммунологические показатели больных хроническим панкреатитом, поскольку автор предполагал решающее влияние иммунологической реактивности организма и ее «поломки» в патогенезе возможных осложнений и летальности в послеоперационном периоде. Для достижения цели клинического наблюдения больные были разделены на 2 клинические группы – 96 пациентов с благоприятным (1-я группа) и 21 пациент с осложенным (2 группа) течением послеоперационного периода (в том числе и умершие пациенты). Полученные данные свидетельствуют о том, что иммунологическая реактивность организма больных в течение послеоперационного периода детерминирует клинический характер его протекания. Это подтверждается благоприятным течением послеоперационного периода у больных с восстановленными после оперативных вмешательств по поводу хронического панкреатита показателями клеточного и гуморального иммунитета, а также его дисбалансом и ареактивностью при формировании послеоперационных осложнений, а также в случае гибели пациентов. Автор заключает, что оценка функционального состояния иммунной системы является решающим критерием в аспекте прогнозирования характера течения послеоперационного периода. Ключевые слова: хронический панкреатит, иммунологическая реактивность, клеточный и гуморальный иммунитет, послеоперационный период, критерии прогнозирования.